Implementation of Branchless Banking in Bogor: a Figure of New Financial Service in Rural Area - Ktut Silvanita Mangani; Yusman Syaukat; Bustanul Arifin; Mangara Tambunan (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Branchless Banking (BB) is a limited financial service provided by financial service providers, such as banks to the customers without having to come to their office. The banks use the third-party called BB Agent and Information Technology. This study aims to provide an overview of the implementation of the BB program in rural areas. This research was carried out in a bank that implemented a BB program. The unit analysis is the BB Agents as an extension of the limited banking services in rural areas and household micro and small businesses conducting financial transactions through the Agents. The method used in this study is descriptive analysis using primary data source through questionnaire.This study was conducted in Bogor District, at 13 Sub-districts. The samples were the BB agents and business households involved in the BB program chosen purposively and analyzed by a descriptive method. The results show that most transactions were in cash and for payment transactions, while savings and cash withdrawal transactions, which are related to production activities, are still minimal. In addition, transactions using digital money (T-Bank) and BSA (Basic Saving Account) as financial products which aims to reach the unbanked communities have not run. Therefore, this study recommends to the Bank to provide adequate education and information to increase public confidence in BB agents. In addition, OJK and BI need to encourage the penetration of BSA products and bring up the culture of digital money in rural areas and encourage the society to utilize the services of financial transactions through BB agents.Keywords: branchless banking, types of transaction, instruments of transaction, digital money, bsaAbstrak: Branchless Banking (BB) adalah jasa keuangan terbatas yang disediakan oleh penyedia jasa keuangan, seperti bank kepada pelanggan, tanpa harus datang ke kantor mereka. Bank menggunakan pihak ketiga (Agen BB) dan Teknologi Informasi. Penelitian ini bertujuan untuk memberikan gambaran tentang implementasi program BB di daerah pedesaan. Penelitian ini dilakukan di bank yang menerapkan program BB. Unit analisis adalah Agen BB sebagai perpanjangan dari layanan perbankan terbatas di daerah pedesaan, serta usaha mikro dan kecil rumah tangga yang melakukan transaksi keuangan melalui Agen BB. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif dengan menggunakan sumber data primer melalui kuesioner. Studi dilakukan di Kabupaten Bogor di 13 Kecamatan. Sampel agen BB dan rumahtangga usaha yang terlibat dalam BB dipilih secara ‘purposive’. Hasilnya menunjukkan bahwa transaksi paling banyak menggunakan uang tunai dan untuk transaksi pembayaran. Transaksi tabungan dan penarikan tunai, yang berkaitan dengan kegiatan produksi masih minimal. Selain itu transaksi menggunakan uang digital (T-Bank) atau BSA (Basic Saving Account) sebagai produk keuangan yang ditujukan kepada masyarakat unbanked belum berjalan. Oleh karena itu, studi ini merekomendasikan kepada Bank untuk melakukan edukasi dan memberikan informasi yang memadai untuk meningkatkan kepercayaan masyarakat kepada agen. Selain itu memberi rekomendasi kepada OJK dan BI untuk mendorong penetrasi produk BSA dan memunculkan budaya uang digital di daerah perdesaan, selanjutnya mendorong masyarakat untuk memanfaatkan jasa transaksi keuangan melalui agen BB.Kata kunci: branchless banking, jenis transaksi, instrumen transaksi, uang digital, BSA